Pembelajaran Akhlak melalui Kitab Akhlaq Lil Banin pada Santri Pondok Pesantren Modern Nurul Amin Parit, Semangat Baru, Kalimantan Barat l Amin Parit, Semangat Baru, Kalimantan Barat - Jamaluddin; Salman Al Farisi (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2024)
Abstract The aims of this study were to (1) analyze the values ​​contained in moral learning through the Akhlaq Lil Baniin book (1) analyze the implementation of moral education through the Akhlaq Lil Baniin book (2) analyze the strengthening of moral learning through the Akhlaq Lil Baniin book for Santri Modern Islamic Boarding School Nurul Amin. This research uses a qualitative approach, uses case study. The results of this study are (1) The moral learning values ​​contained in Lil Banin's Akhlaq book include the santri's morality towards their God, the santri's morality towards their Rosul, the santri's morality towards the ustadz and their teacher, the santri's morality towards their parents, the santri's morality towards their friends, and the morals of the santri towards both those who are smaller and those who are greater than them. (2) The implementation of moral learning through the book of morals lil banin (a) The morals of the santri towards the ustadz or the teacher when in class (b) The morals of the santri towards the ustadz when outside the classroom (c) The morality of the santri when speaking to the ustadz. (3) Efforts to strengthent moral learning are devoted to covering religious values, discipline, love of cleanliness, and family values.